Local Interactions in Aqueous Ethanol Solution Revealed by the C=O Stretching Probe - Zhiqiang Wang; Chi Chen; Ruiting Zhang; Lin Ma; Ke Lin (Molecules)
Accurately identifying local interactions such as hydrophilicity and hydrophobicity is of critical importance in regulating the functions of amphiphilic biomolecules, but in situ identification methods for such interactions are still lacking. This study proposes a probe based on carbonyl (C=O) stretching vibration to study the hydrophilic and hydrophobic interactions in amphiphilic alcohol–water systems. A combination of theoretical calculations and Raman spectroscopy experiments is employed to investigate the molecular interactions of ethyl acetate C=O in an ethanol aqueous solution, as well as the reasons behind the splitting of spectral peaks. The results indicate that the spectral peak splitting of the C=O stretching vibration is attributed to ethyl acetate existing in different hydrophilic and hydrophobic environments. Specifically, the two low-wavenumber components arise from the formation of double and single hydrogen bonds between C=O and water or ethanol, respectively, while the high-wavenumber component is attributed to the interaction between C=O and the hydrophobic alkyl group. These findings suggest that the C=O stretching vibration of esters is sensitive to the surrounding hydrophilic and hydrophobic environments, thereby indicating its potential as a useful probe for identifying hydrophilic and hydrophobic interactions.